2017
DOI: 10.1186/s13287-017-0667-2
|View full text |Cite
|
Sign up to set email alerts
|

Lineage- and developmental stage-specific mechanomodulation of induced pluripotent stem cell differentiation

Abstract: BackgroundTo maximize the translational utility of human induced pluripotent stem cells (iPSCs), the ability to precisely modulate the differentiation of iPSCs to target phenotypes is critical. Although the effects of the physical cell niche on stem cell differentiation are well documented, current approaches to direct step-wise differentiation of iPSCs have been typically limited to the optimization of soluble factors. In this regard, we investigated how temporally varied substrate stiffness affects the step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 19 publications
(22 reference statements)
5
38
0
Order By: Relevance
“…The results showed that distinct colony morphologies were observed depending on the scaffold stiffness, which in turn affected the differentiation tendency of stem cells; iP-SCs cultured on the stiffer substrate tended to differentiate more towards mesendodermal lineage while more ectodermal differentiation was observed on the softer substrate T (Figure 2e-g). Based on these results, the effects of substrate stiffness on the differentiation of iPSCs towards various cell phenotypes throughout various stages were investigated [94]. Results showed that not only the differentiation efficiency of stem cells toward a specific phenotype is significantly affected by substrate stiffness, but the optimal stiffness also dynamically changes during each step of the differentiation process.…”
Section: Mechanically Tuned Polymeric Scaffoldsmentioning
confidence: 99%
“…The results showed that distinct colony morphologies were observed depending on the scaffold stiffness, which in turn affected the differentiation tendency of stem cells; iP-SCs cultured on the stiffer substrate tended to differentiate more towards mesendodermal lineage while more ectodermal differentiation was observed on the softer substrate T (Figure 2e-g). Based on these results, the effects of substrate stiffness on the differentiation of iPSCs towards various cell phenotypes throughout various stages were investigated [94]. Results showed that not only the differentiation efficiency of stem cells toward a specific phenotype is significantly affected by substrate stiffness, but the optimal stiffness also dynamically changes during each step of the differentiation process.…”
Section: Mechanically Tuned Polymeric Scaffoldsmentioning
confidence: 99%
“…Culture of pancreatic progenitors on substrates mimicking the stiffness of the pancreas is a promising strategy to promote differentiation relative to stiff polystyrene. Pancreatic differentiation of hESCs on relatively soft surfaces resulted in increased protein expression of PDX1, and gene expression of pancreatic endoderm markers, NKX2.2 and NKX6.1 ( Narayanan et al, 2013 ; Maldonado et al, 2017 ). Similarly, hESCs encapsulated and differentiated in soft 3D alginate matrices were more viable, proliferative, and had increased PDX1 protein expression suggesting improved pancreatic commitment compared to stiffer gels ( Richardson et al, 2016 ).…”
Section: Cell–matrix Interactionsmentioning
confidence: 99%
“…Using soft, high aspect ratio pillars that promote definitive endoderm differentiation resulted in lower fraction of PDX1 + cells compared to flat, polycarbonate controls while the same substrates has decreased downstream pancreatic differentiation ( Rasmussen et al, 2016b ). Conversely, the formation of PDX1 + cells is promoted on soft electrospun fibers while the precursor mesendodermal cell differentiation is improved on stiffer substrates ( Maldonado et al, 2017 ). Alginate encapsulation of single pancreatic progenitor cells at later stages of differentiation promoted an islet-like gene expression profile and increased the fraction of insulin-expressing cells compared to when PSCs were encapsulated at the beginning of differentiation, further suggesting stage specific optimization of these microenvironmental cues is required ( Legøy et al, 2020 ).…”
Section: Cell–matrix Interactionsmentioning
confidence: 99%
“…Stiffness influences germ layer commitment in ESCs (Zoldan et al, 2011), where softer substrates promote higher expression of endoderm related genes (Sox17, AFP) in both 2D and 3D culture conditions (Jaramillo et al, 2015), and stiffer substrates promote mesodermal gene expression (Brachyury) (Evans et al, 2009; Dado-Rosenfeld et al, 2015). More recently, Maldonado and colleagues reported the development of a semi-3D and spherical arrangement of an iPS cell colony on a softer electrospun nanofiber substrate, as compared to a 2D cell colony on a stiffer substrate (as illustrated in Figure 1B), primarily affected iPS cells during lineage specific differentiation (Maldonado et al, 2016, 2017). They reported enhanced efficiency of biochemically induced mesoendodermal differentiation on stiffer substrates (based on the expression of mesoendodermal lineage markers MIXL1 and Brachyury) as compared to an embryoid body (EB) based differentiation method.…”
Section: Ecm Guided Differentiation Of Stem Cells: Significance Of Mementioning
confidence: 99%